The role of chatbots in paediatric chronic disease management: Trends, findings, and future recommendations - Amelia Arnis; Yeni Rustina; Allenidekania Allenidekania; Fariz Darari (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Chronic diseases in children, such as chronic kidney disease (CKD), diabetes, and asthma require complex long-term management because they can affect the quality of life physically, psychologically, socially, and educationally. One of the new innovations in supporting the management of chronic diseases in children is the use of chatbots that play a role in education, health monitoring, and psychological support. Purpose: To review the literature on the effectiveness of chatbots in supporting self-care in children with chronic diseases. Method: This literature review study examined the effectiveness of chatbots in supporting self-care in children with chronic diseases. The articles used were from ProQuest, Scopus, ScienceDirect, and Google Scholar. Inclusion criteria included publications from 2014-2024 that focused on children with chronic diseases. The search keywords used were "conversational agent", "chronic disease management", and "children". The search for articles used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and obtained 6 articles for review. Results: Analysis of the selected articles suggests that chatbots have the potential to provide easily accessible educational resources, assist in regular monitoring of children's health, and provide emotional support to children in managing chronic diseases. However, there are several challenges, such as limitations in chatbot personalization and the importance of family involvement in chatbot use. Conclusion: Chatbots have great potential to support chronic disease management in children, although further development is needed on the aspects of personalization and data privacy to make their use more effective and safe for children. Suggestion: Long-term research is needed to assess the lasting impact of chatbots on children’s health outcomes, including mental development and quality of life. Developing more personalized and responsive chatbots and exploring their integration with other technologies such as wearables are also interesting areas for further exploration.